Biohydrogen production by novel cyanobacterial strains isolated from rice paddies in Kazakhstan. (30th April 2022) - Kossalbayev, Bekzhan D.; Kakimova, Ardak B.; Bolatkhan, Kenzhegul; Zayadan, Bolatkhan K.; Sandybayeva, Sandugash K.; Bozieva, Ayshat M.; Sadvakasova, Asemgul K.; Alwasel, Saleh; Allakhverdiev, Suleyman I.
Abstract: A limited supply of oil prompts the search for non-traditional energy sources to replace traditional ones. This makes hydrogen gas an appealing alternative source. Photosynthetic organisms capture sunlight very efficiently and convert it into organic molecules. A promising wild strain was isolated for the first time, from the rice paddies of Kazakhstan (Kyzylorda and Almaty regions), which can be considered as one of the most active hydrogen producers compared to the literature. The result showed that among the 13 isolated and collection cyanobacterial strains, Synechocystis sp. S-1 is the most active H2 producer (2.35 μmol H2 mg −1 Chl a h −1 ) in the light. In contrast, the wild-type cyanobacterium Anabaena variabilis A-1 had higher productivity, nitrogenase activity, and a stronger capacity to produce hydrogen in the dark (8.67 μmol H2 mg −1 Chl a h −1 ), which matched the maximum yield obtained in the research. The metabolic modulation performed significantly increased hydrogen production. The highest photohydrogen production rate was observed in cells incubated with 25 μmol HEPES and 50 μmol sodium bicarbonate (NaHCO3 ). Graphical abstract: Image 1 Highlights: Novel cyanobacterial strains were isolated from rice paddies and identified. Сyanobacterial strains have been screened for productivity. Hydrogen production by cyanobacterial strains was examined. Strains were adapted to produce H2 optimizing their physiological properties.